KARAKTERISASI MICRORNA TRIPLE HELIX MELALUI METODE HYDROGEL SCAFFOLD SPESIFIK TERHADAP MICRORNA-26A DAN HSA-MICRORNA-15A: MODALITAS KURATIF MUTAKHIR PADA PENYAKIT KATARAK - Nisrina Hanifa Afnan; Endah Sari R.Kumala; Mochammad Afifuddin (Journal Medical Universitas muhammadiyah Makassar, 2019)
Cataract is an eye disease that is marked by it decrease in lens transparency. Cataract is a major cause of blindness. Data The World Health Organization (WHO) in 2010 showed that there were 285 million people have visual impairments worldwide, 39 million of them blindness where 33% of them are caused by cataracts. Governance cataracts are currently limited to surgical efforts and administration of eye drops as antioxidant. But both have flaws because of the risk of complications limited ocular and lens penetrating ability. Therefore, the author reviewed the potential for triple helix microRNA characterization through specific Hydrogel Scaffold methods against microRNA-26a and hsa-microRNA-15a as the latest curative modalities on cataract disease. microRNA is a non coding RNA molecule consisting of 22 nucleotide. microRNA is known to have a specific target gene so it will increase the effectiveness of therapy in cataracts. The method used in this writing is a study of literature. The author reviews various sources, the majority come from a global journal. The author enters several keywords such as cataract, microRNA, triplex nanoparticle, and Hydrogel Scaffold. The website is used including nature, sciencedirect, pubmed, and ebsco. After extraction based on the inclusion and exclusion criteria that have been determined, the journal is then analyzed and synthesized whose results are written in this review literature. based on literature obtained, microRNA-26a has decreased expression in cataract cases. So that when microRNA-26a is transfected, there will be an increase in regulation which can increase the positive effect on inhibiting the process of fibrosis oncataract pathomechanism mediated by Notch / Jagged-1. Meanwhile, microRNA- 15a overexpresses, so that when transfected antagomir microRNA-15a, then this microRNA will decrease and give negative feedback so the expression of bcl-2 and mcl-1 as antiapoptotic and antioxidant proteins will be increased. To increase its stability, both microRNA-26a and antagomir microRNA-15a will be formed into a triple helix RNA structure through addition dendrimer with the Hydogel Scaffold method. This allows the microRNA become more stable in circulation and can be released in specific genes. By therefore, through the triple helix RNA characterization specific to microRNA-15a and microRNA-26a, cataract therapy is expected to be more effective and efficient. Keywords : cataracts, triple helix microRNA, microRNA-15a, microRNA-2